International perception on student efficiency in Kazakhstan’s educational system (Journal of Educational Sciences, 2021)
The aim of this paper’s background is to show how Kazakhstan’s educational system has changed over the last 30 years of independence, demonstrating modern transformative processes. We also de- fined the goal of establishing the educational level as part of a competence-based approach. Reference analysis, questioning, and experimental work were used as methods. The following are the outcomes: Education quality problems have been revealed, according to the results of a review of Kazakhstan’s state system of vocational education. At this stage of the educational system’s development, it is clear that the concept of learning outcomes in terms of the commitment to competence is critical. The Re- public of Kazakhstan’s recommendations on education quality assurance are made in the context of a competence-based approach. The paper’s innovation is that accuracy issues are considered in the con- text of VET (vocational education and training) and higher education, and each method’s good experi- ence is recommended to be included.As part of the research, a survey of students was conducted on the basis of the Abai KazNPU. 100 respondents took part in the survey. The poll showed that 88% of respondents consider the training system insufficiently consistent with modern standards.All of these issues can be resolved by strengthening the National Qualifications Network in accor- dance with the principles of the European Qualifications Network.Key words: competences, learning outcomes, technical education, National Qualifications Network.